Planning for large epidemics and pandemics: challenges from a policy perspective. Issue 4 (August 2018) - Jain, Vageesh; Duse, Adriano; Bausch, Daniel G.
Abstract : Purpose of review: Less than two decades into the 21st century, the world has already witnessed numerous large epidemics or pandemics. These events have highlighted inadequacies in both national and international capacity for outbreak prevention, detection, and response. Here, we review some of the major challenges from a policy perspective. Recent findings: The most important challenges facing policymakers include financing outbreak preparedness and response in a complex political environment with limited resources, coordinating response efforts among a growing and diverse range of national and international actors, accurately assessing national outbreak preparedness, addressing the shortfall in the global biomedical workforce, building surge capacity of both human and material resources, balancing investments in public health and curative services, building capacity for outbreak-related research and development, and reinforcing measures for infection prevention and control. Summary: In recent years, numerous epidemics and pandemics have caused not only considerable loss of life but also billions of dollars of economic loss. Although the events have served as a wake-up call and led to the implementation of relevant policies and counter-measures, such as the Global Health Security Agenda, many questions remain and much work to be done. Wise policies and approaches for outbreak control exist, but will require the political will to implement them.